Novel Hardware Implementation of the Cipher Message Authentication Code. (21st August 2008) - Michail Michail, H. E. H. E.; Selimis Selimis, G. G.; Galanis Galanis, M. M.; Schinianakis Schinianakis, D. D.; Goutis Goutis, C. E. C. E.
Abstract : A new algorithm for producing message authenticating codes (MACs) was recently proposed by NIST. The MAC protects both a message's integrity—by ensuring that a different MAC will be produced if the message has changed—as well as its authenticity because only someone who knows the secret key could have generated a valid MAC. The proposed security scheme incorporates an FIPS approved and secure block cipher algorithm and was standardized by NIST in May, 2005. In this paper is presented the first efficient hardware implementation of the CMAC standard.